Hubungan math anxiety dengan hasil belajar siswa kelas IV sekolah dasar - Shindy Khalia; Denissa Sri Damayanti; Fia Astri Lani; Keisha Aulia Fadhalah; Arie Rakhmat Riyadi; Neni Maulidah (Trihayu: Jurnal Pendidikan Ke-SD-an, 2026)
Mathematics is an essential subject that shapes the logical thinking of elementary school students. Difficulties in understanding abstract concepts often trigger math anxiety, a worry that reduces learning outcomes. The low mathematical literacy in Indonesia (PISA 2022) is strongly assumed to be related to the high level of students’ anxiety. This study aimed to examine the relationship between math anxiety and learning outcomes of fourth-grade students, as a basis for developing more effective strategies. The research employed a quantitative approach with a correlational design. Anxiety was measured using the Likert-based AMAS questionnaire, and outcomes were from daily test scores. Spearman Rank correlation analysis indicated a strong negative correlation: the higher the anxiety, the lower the cognitive achievement. Significant negative correlations were found in Task 1 (r = -0.878, p = 0.002), Task 2 (r = -0.988, p = 0.000), Task 3 (r = -0.809, p = 0.008), and the exam score (r = -0.988, p = 0.000). The contribution of anxiety to the variation in learning outcomes ranged from 65.44% to 97.61%, with the strongest influence observed in Task 2 and the mathematics exam score.